Translation Today: National Identity in Focus - Kieltyka, Robert; Organ, Michal (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
The book aims to present a comprehensive palette of new approaches and diverse topics in the field of Translation Studies, and specifically discuss various issues correlated with the notion and elements of national identity and their translation. The collection of seventeen selected chapters is intended for researchers, scholars, academics, professional translators and other specialists in the field who direct their attention and practice towards some popular and niche research areas and scientific interests.
Keywords: národní identita; překladatelská činnost; vědecký výzkum; national identity; translating activities; scientific research; elektronické knihy; electronic books